Emphasizing the Role of Human Activities and Extreme Floods in Riverbed Evolution: Inspiration from Hainan Island - Wei Zha; Xiaoqi Chen; Duofeng Wu; Siyang Yao; Zhaonan Li (Journal of Marine Science and Engineering)
Riverbed morphology is in dynamic change due to the influences of both natural and human-induced factors. However, there is a knowledge gap in distinguishing the components caused by human activities as well as extreme flooding from the total riverbed evolution. The current study evaluated the water depth variation in the Nandu River (NR) and Wanquan River (WR) in Hainan Island in response to diverse driven factors. The results showed that the average water depth of both rivers significantly increased, but the spatial-temporal variation patterns were different. In the NR, the dominant spatial-temporal water depth variation was driven by extreme flooding, which contributed 59% to the total variance. Then, water–sediment conditions accounted for 30%, followed by direct human activities for 3.6%. However, the main spatial-temporal water depth variation patterns in the WR were 77%, driven by water–sediment conditions, 10% driven by extreme flooding, and 3.9% driven by direct human interventions, respectively. Considering the indirect effects of human activities on the water–sediment process, the total contributions of human activities on the water depth variation were 6.9% and 42.9% in the NR and WR, respectively. Due to the poor riverbed stability and worse resistance, island rivers are more fragile to extreme floods and human interventions. Our findings suggest that extreme floods usually lead to a significant increase in sediment carrying capacity, followed by severe erosion of the riverbed. In addition, combining with the decrease in sediment concentration and grainsize caused by human activities, the rebuilding effect on riverbeds would be magnified. These results highlight the important role of human activities and extreme floods in the evolution of island rivers, which can provide new insights and recommendations for river management and restoration engineering.